OPTIMASI PELAKSANAAN PENERTIBAN PEMAKAIAN TENAGA LISTRIK (P2TL) SEBAGAI UPAYA PENINGKATAN SAVING KWH DAN PENEKANAN SUSUT NON TEKNIS DI PT. PLN (PERSERO) RAYON SEMARANG SELATAN - Novena Putri, Irene Ega; Subari, Arkhan (Vocational School Diponegoro University, 2015)
Irene Ega Novena Putri, Arkhan Subari, in this paper explain that this study will describe the existing condition P2TL implementation in Rayon South Semarang, examine the root of the problem of lack of optimal implementation of P2TL, and describes efforts to optimizing the implementation in Rayon P2TL South Semarang. The method used is a combination of quantitative and qualitative. The approach used to establish the conditions of implementation P2TL is through observation by setting a good standard P2TL, examining implementation procedures and examined the results of the implementation P2TL P2TL in January-March and discussed the obstacles in its implementation. The approach used to discuss in detail P2TL performance in January-March was through discussion violations committed customers, the amount of saving kWh for three months, the effect of saving kWh in the percentage of shrinkage, and effort optimizing the performance of P2TL. Results of this research note that saving kWh obtained in January-March amounted to 48 599 kWh, or approximately 13% of the targeted savings through the implementation P2TL kWh, thus concluded that the performance P2TL not optimal. Effect of kWh saved is able to suppress shrinkage in January by 0.16% and in March by 0.5%. Efforts should be made in order to optimize the implementation of technically P2TL is through Early Detection of Violations. Efforts should be made in order to optimize the implementation of the non technical P2TL is through targeting of saving kWh monthly, fixing TO Rayon, a sweeping legalization customers, regeneration P2TL implementation team, and socialization prepaid electricity. Keywords: P2TL, shrinkage, saving kWh, TO.